Rare and syndromic tumours in South African children: A novel report from Sub-Saharan Africa - Alessia Pisapia; Guy Shemesh; Derek Harrison (Elsevier, 2025)
Background and Aims: There is a paucity of literature available on the prevalence of paediatric rare and syndromic tumours in Sub-Saharan Africa, furthered by a lack of consensus on the definition of a "rare" tumour. The aim of this study was to describe the types, incidence, management, and overall survival of rare and syndromic tumours in South Africa to improve future management and outcomes. Methods: A retrospective review of patients below 18 years of age presenting to Chris Hani Baragwanath Academic Hospital, South Africa, from the period of 1st January 2004 to 31st December 2017, with rare or syndromic tumours was conducted. Tumours were classified according to criteria described by international literature. (Ethics: M190920) Results: One hundred and eighty-six tumours were identified, with an average incidence of 10 %. The mean age of presentation was 8.3 years. Ten anatomical regions were identified: soft tissue (N = 68, OS= 62 %), head and neck (N = 35, OS= 77 %), renal (N = 19, OS=74 %), skin (N = 17, OS=47 %), hepatic (N = 16, OS=38 %), adrenal (N = 10, OS= 80 %), female reproductive system (N = 8, OS=75 %), pulmonary, chest wall and mediastinum (N = 7, OS=86 %), gastrointestinal (N = 4, OS=75 %) and male reproductive system (N = 2, OS=100 %). The 10 most common variants included: malignant peripheral nerve sheath tumours (N = 15, 8 %, OS=47 %), nasopharyngeal carcinoma (N = 14, 8 %, OS=64 %), malignant melanoma (N = 14, 8 %, OS=43 %), Ewings sarcoma (N = 13, 7 %, OS=54 %), clear cell sarcoma of the kidney (N = 9, 5 %, OS=67 %), hepatocellular carcinoma (N = 9, 5 %, OS=22 %), desmoplastic small round cell tumour (N = 7, 4 %, OS=57 %), synovial sarcoma (N = 7, 4 %, OS=71 %), undifferentiated sarcoma (N = 6, 3 %, OS=66 %), infantile fibrosarcoma (N = 6, 3 %, OS=66 %). Treatment modalities included: surgery (N = 24, 13 %, OS=79 %), palliation (N = 21, 11 %, OS=0 %), surgery and chemotherapy (N = 19, 10 %, OS=58 %), and surgery, chemotherapy, and radiation (N = 16, 9 %, OS=75 %). Thirteen (7 %) were associated with the syndromes: Xeroderma pigmentosa (N = 4, 2 %), Neurofibromatosis (N = 3, 2 %), Tuberous Sclerosis (N = 2, 1 %), Giant congenital nevus syndrome (N = 2, 1 %), Li-Fraumeni (N = 1, 0.5 %) and 31q Deletion syndrome (N = 1, 0.5 %). Overall, there was a 66 % survival rate. Conclusion: The diagnosis of rare tumours in the paediatric population is rising but are rarely associated with a syndrome. Most require definitive surgical treatment; others required the addition of adjuvant chemotherapy and radiation. Overall, although lower than that reported in higher income countries, the prognosis of these tumours remains good. Level of evidence: IV